(Cd)SO4 doping on L-Valine crystal for the enhancement of opto-electronic and laser properties - Susithra, G.; Vidhya, D.; Ramalingam, S. (Physics and Chemistry of Solid State, 2024)
L-Valine is a good molecular platform to induce NLO properties for Laser application and considerable laser properties can be improved by injecting suitable electron administrated substitutional groups. This work is an attempt to make laser properties enhancement by increasing Cd solvent concentration on L-Valine compound. The recorded XRD peaks addressed the significant increment of laser properties of the composite crystal. The results obtained for pure L-Valine was; a=5.221 (Å), b=6.910 (Å) and c=4.994 (Å) and associated indices of refraction was n1=1.511, n2=1.583 and n3=1.599. The results of 2% CdSO4; a=5.580 (Å), b=7.011 (Å) and c=5.091 (Å) and associated indices of refraction was n1=1.561, n2=1.612 and n3=1.633. For 5% CdSO4; a=5.599 (Å), b=7.831 (Å) and c=5.659 (Å) and associated indices of refraction was n1=1.588, n2=1.661 and n3=1.699. For 10 % CdSO4; a=5.592 (Å), b=7.612 (Å) and c=5.822 (Å) and associated indices of refraction was n1=1.661, n2=1.693 and n3=1.593. For 15 % CdSO4; a=5.551 (Å), b=6.332 (Å) and c=4.734 (Å) and associated indices of refraction was n1=1.501, n2=1.599 and n3=1.593. The non linear refractive index was changed from 3.891 X 10-8 cm2/W to 4.231 X 10-8 cm2/W for 2%, 5%, 10% respectively and Third order non linear optical susceptibility (χ(3)) was ranged from 4.621X10‑6 esu to 5.091X10‑6 esu. The restored chemical potential for non linear optical (NLO) and birefringence properties was found to be improved. The scattering capability of homo nuclear and hetero nuclear bonds along with the CdSO4 voids was identified for attaining non linear scattering process.